Corpografias raciais: uma etnografia das captividades femininas negras em São Paulo - Alves, Dina (2020)
This research establishes an intersectional analysis between the punitivist apparatus and anti-black racism, i in black women's urban experiences to access justice in São Paulo. Taking as theoretical-spatial reference recent works that have identified a mortal geography, historically constituted by the “senzala-favela-prison” triad, this research unveils the places of “black captivities” - the street, the house, the prison line, the favela - where black female body is produced and captured as punishable and killable (SPILLERS, 1987 apud ALVES, 2014). In this way, this work proposes to fill a gap left by traditional studies in regard to prisons, as they are studies that do not consider the articulations between categories of oppression - class, race, gender - in criminal justice system. Research suggests that the place occupied by black women in Brazilian society is part of a historical process of subordination, exploration, subjugation and systematic dehumanization of their existence as subjects of rights. In addition to diagnosing a peculiar form of oppression that updates the colonial order, this research aims to answer the following question: how do black women re-signify the meaning of their existence in relation to the penal state and its technologies of domination? Ultimately, the research reveals that deaths, social exclusion, prison and police violence against black women are a fundamental part of the project of contemporary democracy